The horse in my garage and other stories - McManus, Patrick F. (Skyhorse Pub., 2012)
Read about the antics of Patrick<U+2019>s friends Rancid Crabtree and Retch Sweeney in such stories as “Shaping Up for the Hunt” and “Bear Hunters.” McManus plays off the recent obsession with hoarders in his surprising story “The Lady Who Kept Things.” In the titular story, meet Patrick<U+2019>s horse, Huckleberry, and enjoy the experience of all the problems that come along with owning your own horse<U+2014>or keeping him in the garage. Other great stories include: “Catch-And-Eaters,” about the importance of a forked stick when fishing “$7,000 TV Historical Extravaganza,” a look at one director<U+2019>s loose interpretation of historical accuracy and political correctness “A Lake Too Far,” concerning the woes of Patrick and his wife, Bun, on a fateful birding trip in Australia “Chicken Chronicles,” which involves Patrick<U+2019>s memory of wandering around naked in the chicken yard when guests came to call.